Process Development of a Copper(II)-Catalyzed Dehydration of an N-Acyl Prolinal Oxime: Cascade Process and Application at an Elevated Lab Scale - Nonnhoff, Jannis; Gröger, Harald (Synthesis, 2021)
Chiral N-acyl amino nitriles are important structural motifs in several pharmaceuticals such as Vildagliptin or Saxagliptin. Cyanide-free access to such nitriles is provided by a copper-catalyzed dehydration of oximes, which are readily available by condensation of chiral aldehydes resulting from the chiral pool with hydroxylamine. The application in a cascade process without the need for intermediate purification as well as a demonstrated scalability show the robustness of this methodology.
Keywords: aldoximes; cyanide-free nitrile synthesis; dehydration; N-acylaminonitriles; cascade process